Effect of aflatoxin B1 on IgA+ cell number and immunoglobulin mRNA expression in the intestine of broilers. (3rd September 2015) - Jiang, Min; Fang, Jing; Peng, Xi; Cui, Hengmin; Yu, Zhengqiang
Abstract: Aflatoxin B1 (AFB1 ) is the most toxic group of mycotoxins produced by two species of the Aspergillus, common contaminants of food and animal feed. The purpose of our study was to determine the effect of AFB1 on the number of IgA + cell and immunoglobulin mRNA expression in the intestine of broilers. One hundred and fifty six one-day-old healthy Cobb broilers were randomly divided into the control group (the dosage of 0 mg/kg AFB1 ) and AFB1 group (the dosage of 0.6 mg/kg AFB1 ) with three replicates per group and 26 birds per replicate for 21 days, respectively. After necropsy at 7, 14 and 21 days of age, duodenum, jejunum and ileum samples were taken for analyzing IgA + cell by immunohistochemistry and IgA, pIgR, IgM and IgG mRNA expression by qRT-PCR. IgA + cells were mainly distributed in the lamina propria of small intestinal mucosa in both groups at 14 and 21 days of age. A significant decrease in the number of IgA + cells in the duodenum, jejunum and ileum was revealed in the AFB1 group compared with that of the control group. The expression levels of IgA, pIgR, IgM and IgG mRNA in the intestinal mucosa were lower in the AFB1 group than those in the control group at 14 and 21 days of age. Our data demonstrated that the dosage of 0.6 mg/kg AFB1 in broiler diet reduced the number of IgA + cell and the expression of IgA, pIgR, IgM and IgG mRNA in the small intestine.